Anak Putus Sekolah di Kota Pekanbaru: (Studi Kasus Tugas dan Fungsi Dinas Pendidikan Kota Pekanbaru) - Delvia Agustina; Sujianto Sujianto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Riau Province Regional Regulation No. 12 of 2013 concerning the Implementation of Government Education stipulates the 12-Year Learning Obligation. The Pekanbaru City Education Office is an agency authorized to take care of government affairs in the field of education starting from the PAUD, SD, and SMP levels in Pekanbaru City. But in reality there are still problems in the field of education in Pekanbaru City such as school dropouts. This study aims to describe how the implementation of the duties and functions of the Pekanbaru City Education Office in handling dropouts and describe the inhibiting factors in the implementation of the duties and functions of the Pekanbaru City Education Office in handling dropouts. This research uses the theory of administrative functions according to Oey Liang Lee, namely administrative functions consisting of Planning, Organizing, Coordinating, Implementing and Supervising. This research uses descriptive qualitative methods. The data analysis used is data reduction, data presentation and conclusion drawing. The results of this study indicate that the implementation of the duties and functions of the Pekanbaru City Education Office seen from the indicators of planning and organizing has gone well, while from the indicators of implementation, coordination and supervision has not been maximized due to several inhibiting factors such as the lack of training or coaching conducted for educators in SKB, lack of facilities and infrastructure in the activities of the SKB. lack of facilities and infrastructure in the activities of the equivalency education program, coordination meetings that have not been carried out regularly and supervision that has not reached the supervision standards of the Education Office.